Polin : Poles and Jews: Renewing the Dialogue. - Polonsky, Antony (Polin Studies in Polish Jewry Ser., 2004)
In this volume of Polin, scholars from the fields of history, sociology, politics, anthropology, linguistics, literature, and folklore explore central themes in Jewish and European history.